عقـــد العمــــل الرياضـــي - قرباس يمينة بلــباي نادية (جامعة المسيلة, 2020)
عقد العمل الرياضي هو عقد عمل شكلي محدد المدة و ملزم للجانبين (الرياضي، الأجير)، و هو عقد عمل يتسم بالحركة و المرونة أي عدم الديمومة، كما يتميز بخصوصية و ذلك لخضوعه إلى قانون العمل(العمل، الأجر، التبعية)، و كذا للقانون المدني كونه عقد عمل، و إلى قواعد الاحتراف الصادرة عن الاتحادات في المجال الرياضي، في حالة وجود نزاع بين طرفي العقد يحل أولا بالطرقة الودية على مستوى الهيئات(الاتحاد الرياضي، الرابطة) سواء على الصعيد الدولي أو الوطني، واذا لم يحل النزاع يعرض على القضاء، و ينقضي عقد العمل الرياضي بانتهاء أجله، بانجاز العمل المتفق عليه، عند وجود أسباب طارئة، أو بالارادة المنفردة عند اخلال أحد الأطراف بالتزاماته. الكلمات المفتاحية: عقد العمل، عقد العمل الرياضي، الرياضي، الأجير، قواعد الاحتراف. Abstract: The athletic work contract is a formal contract, with limited duration, and binding to both parties (Athlete, Employee). It is a dynamic and flexible work contract, meaning it is non-permenance. It’s distinguished by its relation to the labor law(work, compensation, dependency), and the civil law as a work contract, and to the professionalism rules issued by the federations in the athletic domain. In case of a conflict between the two contracted parties, the conflict will be first resolved amicably at the level of organizations (Athletic Federation, The League) whether at the international or national level, if the conflict is not resolved, it will be brought to justice. The athletic work contract will expire upon its expiry date, upon the completion of the work agreed on, in case of unforeseen circumstances, or by individual willingness when either party breaches its obligations. Key words : work contract , athletic work contract, Athlete, Employee , the professionalism rules issued .
Keywords: عقد العمل، عقد العمل الرياضي، الرياضي، الأجير، قواعد الاحتراف